Massive Carbamazepine Poisoning - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The clinical features in 28 consecutive adult cases of laboratory confirmed massive overdosage with CBZ alone treated in an intensive care unit during the period 1981-1991 are reported from Southern Hospital, Karolinska Institute, Stockholm, Sweden.